A Research on the Application of Multimedia Technology in Bilingual Teaching of International Politics - Baisong Wang, (IJRDO- Journal of Educational Research, 2020)
The multimedia technology is a new modern teaching means. The flexible application of multimedia technology in the bilingual teaching of international politics, to acertain extent, will reduce the difficulty of the bilingual teaching, help the students understand professional knowledge and stimulate their enthusiasm for international politics and the related knowledge. But bilingual teaching through multimedia also has many problems. The improvement path of multimedia teaching can be found by exploring and researching, thus the teaching quality and effect of bilingual teaching in international politics will also be improved.